Targets Tax Shelter Participation and Takeover Premiums - CHOW, Travis (Institutional Knowledge at Singapore Management University, 2016)
This paper examines the effect of targets' participation in tax shelters on takeover premiums in mergers and acquisitions. Using a novel data set in which targets disclose that they have not participated in tax shelters, we find that targets that make this statement in their merger filings are associated with 4.6 percent higher takeover premiums, on average. These findings suggest that acquirers are concerned about the potential future liabilities when targets have engaged in tax sheltering. Consistent with this interpretation, the results also indicate that the positive association between targets' nonsheltering disclosure and acquisition premiums is stronger for less tax-aggressive acquirers. This paper demonstrates the importance of targets' aggressive tax positions in the determination of premiums offered to targets' shareholders.